The Impact of University Internal Environment, Development Talents on Sustainable Competitive Advantage - Lazim, Yusra Yaseen (South Asian Journal of Social Sciences and Humanities, 2023)
There is a need to make serious efforts For Iraqi universities to be in the ranks of advanced universities in the world. This requires attracting teaching talents and providing an incubating environment for them. Therefore, the objective of the research was to explore the influence of (the environment, the development of talents) on sustainable competitive advantages. The research followed the descriptive approach and used the quantitative analysis method. Almaqaal university is the field of study. The study sample size (of 76 people), from almaaqal university teachers, and the sample comprised the available staff specialized in the field of Teaching and research. The questionnaire was utilised as a data collection tool and (spss) program was the main program used in the analysis. Methods of attracting talents and providing an incubating environment for talents contribute to the development of talents on the one hand, and to strengthening the positive link among the university and society on the other influence. Iraqi universities still lack methods of attracting and nurturing talent. In addition to the lack of studies dealing with this subject, this study provides a theoretical and practical addition to Iraqi studies in this field. The improvement of university outputs also reflects positively on the national economy and sustainable development.